Using admixture analysis to examine birth‐cohort effects on age at onset of bipolar disorder. (7th August 2015) - Golmard, J.‐L.; Scott, J.; Etain, B.; Preisig, M.; Aubry, J.‐M.; Henry, C.; Jamain, S.; Azorin, J.‐M.; Leboyer, M.; Bellivier, F.
Abstract : Objective: It is suggested that age at onset (AAO) of bipolar I disorder (BP‐I) is decreasing. We tested for a birth‐cohort effect on AAO using admixture analysis. Method: A clinical sample of 3896 BP‐I cases was analysed using two approaches: (i) in a subsample with untruncated AAO × birth year distribution ( n = 1865), we compared the best‐fitting model for the observed AAO in patients born ≤1960 and >1960, (ii) to control for potential confounders, two separate subsamples born ≤1960 and >1960 were matched for age at interview ( n = 250), and a further admixture analysis was undertaken. Results: The two approaches indicated that the proportion of cases in the early AAO category was significantly greater in cases born >1960; manic onsets were also more frequent in the early onset BP‐I cases born >1960. Conclusion: The decrease in AAO of BP‐I in recent birth‐cohorts appears to be associated with an increase in the proportion of cases in the early onset subgroup; not with a decrease in the mean AAO in each putative subgroup. This could indicate temporal changes in exposure to risk factors for mania.